Foraging Habits of Green Sea Turtles (Chelonia mydas) in the Northwestern Gulf of Mexico - Howell, Lyndsey N.; Shaver, Donna J. (Frontiers in Marine Science, 2021)
Knowledge of green turtle (Chelonia mydas) foraging ecology in the northwestern Gulf of Mexico (GOM) is critical as populations begin to recover from heavy harvesting in prior centuries. We present a comprehensive long-term assessment of green turtle diets from carcasses salvaged from 1987–2014 along the Texas coast. Digestive tract contents were examined from 420 green turtles, ranging in size from 7.3 to 86.0 cm in straight carapace length (SCLmax). Green turtles as small as 16.2 cm SCLmax recruit from the oceanic environment to nearshore foraging habitat in the northwestern GOM and consume macroalgae principally. A successive shift in diet and habitat to inshore seagrasses was evident by the seagrass-dominated diet of turtles larger than 30 cm SCLmax. Animal matter remained a frequently ingested diet item suggesting these immature green turtles are better classified as omnivores. The overall evidence indicates that Texas' recovering green turtle assemblage is exhibiting foraging plasticity within seagrass meadows changing species composition and density.